2013
DOI: 10.2147/ndt.s42745
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone, quetiapine, and olanzapine adjunctive treatments in major depression with psychotic features: a comparative study

Abstract: ObjectivesThe purpose of this study was to compare the effectiveness of novel antipsychotics in the treatment of psychotic depression.MethodConsecutive patients who were admitted (n = 51) with a confirmed diagnosis of major depression with psychotic features (delusions or hallucinations or both) participated in this open-label, naturalistic study. All patients were treated with selective serotonin reuptake inhibitors (SSRIs) and serotonin-norepinephrine reuptake inhibitors (SNRIs) (citalopram or venlafaxine ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…10 A number of studies have found combination therapy with antidepressants plus second-generation antipsychotics (e.g., olanzapine, quetiapine, aripiprazole, and risperidone) to be effective in achieving a response or remission of depressive episode symptoms in psychotic depression. [14][15][16][17][18][19][20][21] Combination therapy is more beneficial when compared with antipsychotic monotherapy, 16,21 while the results are not as clear when combination therapy is directly compared with antidepressant monotherapy. 14,15,22 For example, a meta-analysis found that combination therapy with an antidepressant plus antipsychotic was superior to antidepressant monotherapy in relation to study-defined inefficacy and Clinical Global Impressions scores.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…10 A number of studies have found combination therapy with antidepressants plus second-generation antipsychotics (e.g., olanzapine, quetiapine, aripiprazole, and risperidone) to be effective in achieving a response or remission of depressive episode symptoms in psychotic depression. [14][15][16][17][18][19][20][21] Combination therapy is more beneficial when compared with antipsychotic monotherapy, 16,21 while the results are not as clear when combination therapy is directly compared with antidepressant monotherapy. 14,15,22 For example, a meta-analysis found that combination therapy with an antidepressant plus antipsychotic was superior to antidepressant monotherapy in relation to study-defined inefficacy and Clinical Global Impressions scores.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…It is generally concluded that there is similar satisfactory clinical efficacy in terms of mental state and global functioning across the FGAs and second-generation antipsychotics 3437. However, a few trials indicate the superiority of individual second-generation agents over the FGAs in specific illness condition or patient outcomes 29,33,37,38. In two meta-analyses of placebo-controlled trials,39,40 haloperidol was reported to be less effective in reducing symptoms and/or relapse than certain second-generation agents (eg, clozapine and olanzapine).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…The FDA has approved both quetiapine and aripiprazole as well as the combination of olanzapine with fluoxetine for augmentation. Other agents include ziprasidone and risperidone, which have also been shown to be effective in treating MDD/TRD (Gabriel, 2013 ; Nelson, 2015 ).…”
Section: Adjunctive Biological Options For Treating Trd Alongside Antmentioning
confidence: 99%